PS-053 System for improving adherence in polymedicated patients. (24th February 2014) - Marmesat, B; Gallego, M; Fernández, I; Villa, A; Guerra, D; Márquez, E; Ramos, JJ
Abstract : Background: Polymedicated patients are susceptible to medicines errors. Ensuring good compliance through medicines reconcilliation and follow-up after hospital discharge may be useful in improving control of chronic diseases and patient safety. Purpose: To assess the degree of compliance with chronic treatment prescribed at discharge and to determine the degree of satisfaction of the monitoring and support of polymedicated patients at home. Materials and methods: Interventional study conducted by a multidisciplinary team consisting of the Pharmacy Service, Inpatient Nursing Unit and doctors from Internal Medicine. We included all patients over 60 years old on active treatment with 6 or more drugs, and stable home treatment, who were admitted to the Internal Medicine Department from November 2012 to July 2013. The intervention consisted of reconciliation of home treatment on admission and at discharge, which provided oral information and written instructions to follow at home. Three weeks after discharge, the pharmacist made a home visit where the changes to the discharge medicines were checked and the degree of compliance with the treatment was verified. The patient was considered to have good adherence when the consumption of the prescribed tablets was between 80 and 110%. One month after the visit, a telephone survey was conducted by an external professional of the project, in which the patient, family and/or caregiver could assess the information provided, professionalism and overall satisfaction with the service. Results: We included a total of 74 patients, 62.2% (46) of whom were women, with a mean age of 77.8 ± 6.8; 27% (36) were functionally dependent patients (moderate, severe or complete) according to the Barthel index. 47% were taking between 10 and 14 drugs at home. After interviewing the patients at home, the recorded degree of compliance was 94.6% (70) of the studied population. 70.3% (52) of those visited completed the satisfaction survey, of whom 65.4% (34) were family/caregiver and 34.6% (18) patients. 86.5% (45) of the patients appreciated the professionalism of the team. 78.8% (41) considered that the information provided had been helpful. Finally, 94.2% (49) of the patients expressed overall satisfaction with the service. Conclusions: The reconciliation process at discharge, with individual attention and subsequent monitoring at the patient's home could ensure appropriate compliance with chronic treatment, with a consequent reduction in medicines errors and adverse effects. No conflict of interest.